Peran Mata Kuliah Etika Profesi Terhadap Perkembangan Perilaku Etis Mahasiswa - Susi Chairani; Nurhazana Nurhazana (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2020)
This study aims to determine: 1) the role of professional ethics course in the development of student ethical behavior 2) the development of ethical behavior of student after taking professional ethics courses 3) different in the development of ethical behavior of younger students and older students. The sample in this study were 160 students of the Public Financial Accounting study program at the Bengkalis Polytechnic.Data collection techniques is questionnaires and documentation. The type of research is descriptive quantitative. The data analysis methods is regression analysis, descriptive statistics, and the Mann-Whitney test with the help of the SPSS version 25 program. The result showed that: 1) the role of professional ethics courses has a positive effect on the development of ethical behavior 2) The development of ethical behavior of student after taking professional courses is in the fairly good category 3 there is no difference in the development of ethical behavior of younger students with older students.